Antibacterial Activity of Ethanolic Extract of Pandanus Nut (Pandanus julianettii) Gastrointestinal Bacteria Using The Agar Diffusion Method - Monika, Arum; Naid, Tadjuddin; Herwin, Herwin (Fakultas Farmasi, Universitas Muslim Indonesia, 2025)
Gastrointestinal infections are a major global health concern, often caused by pathogenic bacteria. This study aimed to evaluate the antibacterial activity of the ethanolic extract of Pandanus nut (Pandanus julianettii) against gastrointestinal pathogens using the agar diffusion method. The Minimum Inhibitory Concentration (MIC) of the extract was determined to be 6.4% for Shigella dysenteriae, Salmonella typhi, and Escherichia coli, and 3.2% for Vibrio cholerae. The Minimum Bactericidal Concentration (MBC) for all tested bacteria was 12.8%. Antibacterial activity analysis revealed that at the 12.8% concentration, the largest inhibition zones were observed: 22.68 mm for Salmonella typhi, 22.20 mm for Shigella dysenteriae, 21.26 mm for Escherichia coli, and 20.80 mm for Vibrio cholerae. These findings indicate that the ethanolic extract of Pandanus julianettii possesses strong antibacterial properties and holds potential as a natural therapeutic agent for managing gastrointestinal infections.